STUDENTS’ PERCEPTION ON THE USE OF ZOOM MEETING AS ONLINE MEDIA TOOL AT THE ENGLISH EDUCATION DEPARTMENT STUDENTS OF UNIVERSITAS RIAU BATCH 2020 - Ramadani, Nindi; Erni, Erni; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to find out English students’ perception on the use ofZoom Meting as online media tool. Purposive sampling technique was applied to decide the sample. There were 79 students as the participants. The instrument used was a questionnaire categorized into 8 components of perception such as self-efficacy,satisfaction, usefulness, behavioral intention, Zoom Meeting system quality, interactivelearning activities, Zoom Meeting effectiveness, and Zoom Meeting instruction. Thefinding shows that English students from admission year 2020 have a positive perceptionon the use of Zoom Meeting as online media tool. It showed that students put positiveperception of self-efficacy, satisfaction, usefulness, behavioral intention, Zoom Meetingsystem quality, interactive learning activities, Zoom Meeting instruction. While studentshave neutral perceptions of Zoom Meeting effectiveness. The students are suggested to be more active in using Zoom Meeting in their learning process as it helps them to make the learning process more effective.Key Words: Zoom Meeting, Perception, Online Media Too